P-140 Musical chairs – more than just an exercise group. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Jones, Dympna; Marley, Kate; Forshaw, Clare; McIntegart, Kate; Cunliffe, Helen; Clarkson, Susan
Abstract : Background: The benefits of exercise for people with life-limiting conditions are widely recognised. Woodlands Hospice runs a weekly exercise group which is well attended. Feedback is positive and the environment provides more than simply physical benefits. It has become a safe place that instils positivity and humour where patients can share feelings and coping strategies, gain support and strength from their peers and staff, ask for help whether physical, emotional or spiritual and where they can just 'be'. Aim: To further develop this group to enhance the experience for patients. Specifically: Music. To introduce music in the form of a personal group playlist where all patients are involved in sharing a song and a reason for its choice. This music is played during the group and made available to take home. Tai Chi. To teach simple chair based Tai Chi to be practised at the end of each session to promote a calm and contemplative atmosphere. Palliative Outcome Scale (POS). Using this recognised tool on a monthly basis helps patients to discuss any new concerns, allows staff to signpost patients appropriately and streamlines outcomes throughout the hospice. Methods: Literature review on clinical benefits of Music therapy and Tai Chi Consultation with group members Practise Tai Chi sessions Multidisciplinary consultation regarding introduction of POS. Results: Music A feeling of ownership and camaraderie promoting discussion ranging from shared memories to the spiritual needs of the present Tai Chi This new skill has facilitated relaxation, breathing control and aided sleep POS Its use has identified a gap in care when patients are not accessing other hospice services and ensured their needs are met. Conclusion: The exercise group has proved to be a good leveller with patients feeling confident to share experiences whilst gaining physical and emotional strength.